Hypoxia-Induced Reactive Oxygen Species: Their Role in Cancer Resistance and Emerging Therapies to Overcome It - Eleicy Nathaly Mendoza; Maria Rosa Ciriolo; Fabio Ciccarone (Antioxidants)
Normal tissues typically maintain partial oxygen pressure within a range of 3–10% oxygen, ensuring homeostasis through a well-regulated oxygen supply and responsive vascular network. However, in solid tumors, rapid growth often outpaces angiogenesis, creating a hypoxic microenvironment that fosters tumor progression, altered metabolism and resistance to therapy. Hypoxic tumor regions experience uneven oxygen distribution with severe hypoxia in the core due to poor vascularization and high metabolic oxygen consumption. Cancer cells adapt to these conditions through metabolic shifts, predominantly relying on glycolysis, and by upregulating antioxidant defenses to mitigate reactive oxygen species (ROS)-induced oxidative damage. Hypoxia-induced ROS, resulting from mitochondrial dysfunction and enzyme activation, exacerbates genomic instability, tumor aggressiveness, and therapy resistance. Overcoming hypoxia-induced ROS cancer resistance requires a multifaceted approach that targets various aspects of tumor biology. Emerging therapeutic strategies target hypoxia-induced resistance, focusing on hypoxia-inducible factors, ROS levels, and tumor microenvironment subpopulations. Combining innovative therapies with existing treatments holds promise for improving cancer outcomes and overcoming resistance mechanisms.